2017
DOI: 10.1186/s13098-017-0234-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene variants in the FTO gene are associated with adiponectin and TNF-alpha levels in gestational diabetes mellitus

Abstract: BackgroundObesity may have a role in the development of gestational diabetes mellitus (GDM). Single-nucleotide-polymorphisms (SNPs) of the FTO (fat mass and obesity associated) gene have been associated with obesity. The aim of this study was to investigate SNPs rs8050136, rs9939609, and rs1421085 of the FTO gene in women with GDM and their associations with maternal pre-pregnancy weight and body mass index, gestational weight gain and mediators of insulin resistance in GDM like leptin, adiponectin, ghrelin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 50 publications
2
12
0
4
Order By: Relevance
“…For example, Zimmermann et al (2011) found in young Danish men that the FTO risk allele, rs9939609, which has a strong linkage disequilibrium with rs1421085, was associated with increased CRP level but had no impact on IL-1, IL-6, and TNFa. However, rs9939609 was associated with increased TNFa in Mexican women with gestational diabetes (Saucedo et al, 2017). The impact of rs9939609 on the fasting and postprandial level of IL-6 and TNFa in Brazilian women revealed that, in the fasting stage, levels of IL-6 and TNFa were similar for the A and T risk alleles but in the postprandial period, while TNFa was not altered in individuals with AA genotype compared to TT and TA genotypes, the serum levels of IL-6 and ghrelin were low and those of leptin were high (Magno et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…For example, Zimmermann et al (2011) found in young Danish men that the FTO risk allele, rs9939609, which has a strong linkage disequilibrium with rs1421085, was associated with increased CRP level but had no impact on IL-1, IL-6, and TNFa. However, rs9939609 was associated with increased TNFa in Mexican women with gestational diabetes (Saucedo et al, 2017). The impact of rs9939609 on the fasting and postprandial level of IL-6 and TNFa in Brazilian women revealed that, in the fasting stage, levels of IL-6 and TNFa were similar for the A and T risk alleles but in the postprandial period, while TNFa was not altered in individuals with AA genotype compared to TT and TA genotypes, the serum levels of IL-6 and ghrelin were low and those of leptin were high (Magno et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…Three SNPs within the FTO gene were studied for GDM. Of the six studies investigating rs9939609, one study in a Finnish population found an association between the A allele and an increased risk for GDM [ 44 ], another study in a small Spanish population found an association between the T allele and GDM [ 41 ], while four studies reported no association [ 38 , 39 , 47 , 70 ]. Discrepancies between the studies are possibly due to ethnic and genotyping method differences.…”
Section: Single-nucleotide Polymorphismsmentioning
confidence: 99%
“…Discrepancies between the studies are possibly due to ethnic and genotyping method differences. None of the studies investigating rs8050136 and rs1421085 found an association between these SNPs and GDM [ 45 , 47 , 70 ].…”
Section: Single-nucleotide Polymorphismsmentioning
confidence: 99%
“…suggested that lower concentrations of adiponectin and higher concentrations of pro-inflammatory tumor necrosis factor-alpha were associated with the FTO rs9939609 risk allele A in women with gestational diabetes mellitus after adjusting for maternal pregestational body weight. [ 31 ] Furthermore, recently, a study observed that the carriers of risk allele A of FTO Polymorphism rs9939609 had increased CRP and insulin values. [ 32 ] However, some studies did not report an association between the FTO rs9939609 variant and inflammatory state.…”
Section: Discussionmentioning
confidence: 99%